Peningkatan Kemampuan Berbahasa Reseptif Anak Usia 5-6 Tahun Melalui Media Gambar - Fally Manafe; Supriadi Supriadi; Ashar Ashar (PG PAUD Universitas Islam Makassar | LP2M-UIM | PPJ PAUD (Perhimpunan Pengelola Jurnal PAUD) Indonesia, 2025)
This research is motivated by the low receptive language skills of children aged 5-6 years, especially in the aspect of recognizing letter symbols and understanding simple sentence structures. This study aims to improve children's receptive language skills through the use of picture media at Bina Kasih Kindergarten Makassar. The type of research used is Classroom Action Research (CAR) with the Kemmis and McTaggart model which includes the stages of planning, implementation, observation, and reflection. The research subjects were 8 students with data collection techniques including observation, interviews, and documentation. Data analysis was carried out descriptively to measure the percentage increase in children's reading ability at each stage of the cycle. The results showed a significant increase in children's receptive language skills gradually. In the pre-action condition, the average ability of children only reached 37.5% in the indicator of reading letter symbols and 34.3% in the indicator of reading syllables and sentences. After the intervention in Cycle I, children's abilities increased to 78% for reading letter symbols and syllables, and 62.5% for reading sentences. At the end of Cycle II, success peaked at 100% for symbol and syllable reading, and 93.75% for sentence reading. The use of visual media proved highly effective due to its concrete and realistic nature, attracting attention, clarifying understanding, and strengthening children's memory of new vocabulary. This study concluded that the creative and consistent application of visual media can optimally stimulate receptive language development in early childhood.